1964
DOI: 10.1128/aem.12.2.165-168.1964
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of Manganese for Tomato Juice in the Cultivation of Lactic Acid Bacteria1

Abstract: Substitution of manganese for tomato juice in the cultivation of lactic acid bacteria. Appl. MIicrobiol. 12: 165-168. 1964. Tomato juice was separated by chemical and physical methods into various active fractions, as measured by growth response and acid production by numerous lactic acid bacteria. Incineration of the treated extracts with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1965
1965
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…Manganese is also an important growth factor for the oral streptococci and lactobacilli. Stamer et al (15) demonstrated that more than 88% of lactic acid bacteria tested exhibited a requirement for manganese. Bowen (6) showed that manganese was the only transition metal required for growth of cariogenic and noncariogenic streptococci.…”
mentioning
confidence: 99%
“…Manganese is also an important growth factor for the oral streptococci and lactobacilli. Stamer et al (15) demonstrated that more than 88% of lactic acid bacteria tested exhibited a requirement for manganese. Bowen (6) showed that manganese was the only transition metal required for growth of cariogenic and noncariogenic streptococci.…”
mentioning
confidence: 99%
“…L. citrovorwn ML 34 was obtained from Ralph E. Kunkee, Department of Enology, University of California, Davis. The culture was maintained in a tryptone-glucose-yeast extract-salts medium (TGYE) supplemented with tomato juice (10%) as previously described (15).…”
Section: Methodsmentioning
confidence: 99%
“…The semi-solid medium of Gibson and Abdel-Malek (1945) as modified by Stainer et al (1964) was used. Twenty millilitres of the medium were dispensed into MacCartney bottle and sterilized.…”
Section: Homofermentative and Heterofermentative Testmentioning
confidence: 99%